2012
DOI: 10.1080/13691058.2012.710762
|View full text |Cite
|
Sign up to set email alerts
|

Young women's management of victim and survivor identities

Abstract: Images of child sexual abuse survivors have been strongly mediated by professional and self-help ideologies that espouse 'healthy' and 'unhealthy' responses to trauma. Drawing on interviews taken with five self-identified survivors of child sexual abuse, this paper maps the impact of psychological and popular discourses on victim/survivor identities and, in particular, the centrality of themes such as disclosure and 'healing' in accounts from survivors. Investment in these particular versions of recovery has o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Hunter (2010) referred to these individuals as having a transcendent narrative. Those who choose neither often indicate that they believe both labels have come to be associated with presumed psychopathology (e.g., depression, anxiety, posttraumatic stress disorder) resulting from their assault (Ovenden, 2012). Regarding life choices, hobbies, and deviant behavior such as drug use, interviewees in Ovenden’s study expressed discomfort about the assumptions others seemed to make with either label.…”
Section: Victim and Survivor Labelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hunter (2010) referred to these individuals as having a transcendent narrative. Those who choose neither often indicate that they believe both labels have come to be associated with presumed psychopathology (e.g., depression, anxiety, posttraumatic stress disorder) resulting from their assault (Ovenden, 2012). Regarding life choices, hobbies, and deviant behavior such as drug use, interviewees in Ovenden’s study expressed discomfort about the assumptions others seemed to make with either label.…”
Section: Victim and Survivor Labelsmentioning
confidence: 99%
“…There is also the assumption that those who have experienced sexual assault all have the same experiential response to their assault with potentially traumatic levels of long-lasting stress that needs to be addressed therapeutically. Although those with a transcendental narrative seemed to view the event as horrific and injurious at the time it happened, they often report that their experience (after time had passed) was no longer so intrusive and that they did not care to label it or even think of it (Hunter, 2010; Ovenden, 2012).…”
Section: Victim and Survivor Labelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants spoke about the victim/survivor dialectic and mirrored the common practice in RCC counseling to use the word “survivor” over “victim” as it is considered the more respectful and empowering label. Although much has been written on these terms from an empowerment perspective (Hockett & Saucier, ; Ovenden, ; Young & Maguire, ), there has been less focus on how this dichotomy upholds a neoliberal ideology. Participants often spoke about how to help survivors “feel” more in control or have a “sense” of agency; using the language of “survivor” was one example.…”
Section: Discussionmentioning
confidence: 99%
“…Other early work suggested that beliefs in conspiracy theories serve self-esteem maintenance purposes (Young, 1990; Robins and Post, 1997), while providing believers an outlet for reasserting their individualism (Melley, 2000) or for the expression of negative feelings (Hofstadter, 1965; Ungerleider and Wellisch, 1979). Recently Swami and Furnham (2012) found conspiracy beliefs in one famous story- the disappearance of Amelia Earheart- were associated with lower self-esteem and lower self-estimated intelligence.…”
Section: Commercial Conspiracy Theoriesmentioning
confidence: 99%